2006
DOI: 10.1007/s10800-006-9179-y
|View full text |Cite
|
Sign up to set email alerts
|

Formic acid oxidation on Pd-modified Pt(100) and Pt(111) electrodes: A DEMS study

Abstract: Formic acid oxidation on palladium submonolayers on well-defined Pt(100) and Pt(111) electrodes has been studied using voltammetry and Differential Electrochemical Mass Spectrometry (DEMS). A combination of the two techniques allows a better understanding of the reaction taking place on the electrode surface. Thus, an exact correlation between the CO 2 mass signal and the current density in the voltammogram corresponding to the formic acid oxidation has been obtained. On palladium modified Pt(100) electrodes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 34 publications
3
26
0
Order By: Relevance
“…Fast poisoning was also observed on Pd ML-Pt (100) single crystals, and was attributed to the formation of blocking species on the Pd sites by a different mechanism than the one occurring on Pt [51]. The fact that sulfuric acid was used may also add some extra complications since a recent study suggested that the adsorption of (bi) sulfate anions has an inhibiting behavior on the formic acid oxidation reaction [52].…”
Section: Comparison Of Activity For the Oxidation Of Formic Acidmentioning
confidence: 99%
“…Fast poisoning was also observed on Pd ML-Pt (100) single crystals, and was attributed to the formation of blocking species on the Pd sites by a different mechanism than the one occurring on Pt [51]. The fact that sulfuric acid was used may also add some extra complications since a recent study suggested that the adsorption of (bi) sulfate anions has an inhibiting behavior on the formic acid oxidation reaction [52].…”
Section: Comparison Of Activity For the Oxidation Of Formic Acidmentioning
confidence: 99%
“…Alloying of Pd with the second metal changes the surface electronic state, resulting in an ensemble effect, which can possibly reduce the catalyst poisoning and increase the activity and lifespan of the catalyst. A number of studies have been carried out recently with the aim to design multi-component Pd catalysts [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Approaches include the deposition of sub-monolayers of Pd on various supports, such as V, Mo, W and Au [26], Pt and Au single crystals [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been carried out recently with the aim to design multi-component Pd catalysts [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Approaches include the deposition of sub-monolayers of Pd on various supports, such as V, Mo, W and Au [26], Pt and Au single crystals [27][28][29][30][31]. Both Pd-Pt bulk and nano-catalysts [22][23][24][25][26][27][28][29][30][31][32][33][34][35] show high activity and improved stability in DFAFCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the electrochemical oxidation of formic acid has been attracting increasing attention [1][2][3][4][5][6] because the direct formic acid fuel cell (DFAFC) has some advantages over the direct methanol fuel cell [7,8]. For example, formic acid is non-toxic and nonflammable.…”
Section: Introductionmentioning
confidence: 99%